Fundacentro: função social da política sobre acidentes de trabalho no período ditatorial brasileiro (1966 a 1976) - Monteiro, Juliana Santos (2013)
This work is aimed at understanding the policy developed by the dictatorial government between the years 1966 and 1976, Safety and Health at Work, created by Fundacentro. Fundacentro is an institution of research and studies related to safety, hygiene and occupational medicine, coupled with the Ministry of Labor. Fundacentro had great relevance in the period mentioned, and, among their responsibilities there is one which is highlighted by the social function it accomplished. Firstly, it was to provide technical accessory to the Legislature and the Executive in order to have the development of safety standards at work. Secondly, it was to coordinate and promote the professionals chiefly specialized in security and health in the area, implemented by official policy. Fundacentro ran as a tripartite organization and was directed by a Board of Councils, which was held by government representatives, entrepreneurs and workers. The correlation between social groups involved in Fundacentro since it was created had no equality in terms of the entrepreneurship, the government, the academics1 and trade unions, together with international bodies like the International Labor Organization (ILO) and their respective interests in the structuring the Health and Safety in Brazil. In a period in which Brazil was considered the champion in work accidents, their main function was to provide technical support and educational prevention policy. It was defined by the government, which stemmed from the assumption that the accidents were caused by the workers themselves. This evidence is taken from the immanent analysis of sources: publications by Fundacentro, as the Newsletter and the Brazilian Journal of Occupational Health (Revista Brasileira da Saúde Ocupacional), prevention information disseminated by the institution Fundacentro. They are based on concepts related to the Unsafe Act of the worker, blaming himself for the accidents. We finally understand that, the powers of the institution at that time were consistent with the National Security Doctrine